ANALISIS OPTIMASI RUTE DISTRIBUSI BARANG MENGGUNAKAN VEHICLE ROUTING PROBLEM (VRP) MODEL SWEEP METHOD PADA PT. XYZ - Anisa Nur Rohmah (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
Distribution activities are critical for ensuring efficient and timely delivery of goods to consumers. Transportation problems arise when companies must determine cost-effective delivery routes with optimal travel time. This study determines the most efficient transportation routes for PT. XYZ in serving 12 customer points from a single depot using the Vehicle Routing Problem (VRP) approach with the Sweep Method. Data include customer locations, geographic coordinates (X-Y), and demand quantities, processed using Microsoft Excel through coordinate conversion to polar format and systematic sweeping for route optimization. This research differs from previous studies by integrating actual customer geographic data in Bandung with the Sweep Method, simultaneously considering vehicle capacity and demand distribution to produce a realistic and applicable route model for logistics companies. Results show four optimal routes with a total distance of 106.27 km and delivery capacity of 510 units per day, reducing transportation costs and enhancing overall distribution efficiency.